Clinical scoring model based on age, NIHSS, and stroke-history predicts outcome 3 months after acute ischemic stroke - Ding, Gang-yu; Xu, Jian-hua; He, Ji-hong; Nie, Zhi-yu (Frontiers in Neurology, 2022)
Background: To establish a simple and effective clinical prediction model to predict the 3-month prognosis of acute ischemic stroke. Methods: 132 eligible participants constituted a prospective study cohort. Least absolute shrinkage and selection operator regression was applied to select features associated with poor prognosis. On this basis, the nomogram was drawn and evaluated for discriminative power, calibration, and clinical benefit, and validated internally by bootstrap.The optimal cutoff point for each independent risk factor and nomogram was calculated by the Youden index. Results: Five factors affecting the 3-month prognosis of acute ischemic stroke were screened by lasso regression. Good outcome was found in 94 (71.212%) patients and bad outcome in 38 (28.788%) patients during the follow-up period. A total of 8 (6.061%) deaths were reported over this period, of whose 5 (3.788%) were died during hospitalization. Multivariate logistic regression revealed 3 independent risk factors affecting patient outcomes, namely age, previous stroke, and NIHSS. The AUC of the nomogram was 0.880(95%CI, 0.818-0.943), suggesting that the model has good discriminative power.The p-value for the calibration plot is 0.925, indicating that the model is well calibrated. When the threshold probability is greater than 0.01, the net benefit obtained is the largest.The C-index for 1000 bootstrapping calculations is 0.869. The age cutoff for predicting poor patient outcomes was 76.5 years (specificity 0.777, sensitivity 0.684), the cutoff for the NIHSS was 7.5 (specificity 0.936, sensitivity 0.421), and the cutoff for total nomogram score The point was 68.8 (sensitivity 81.6%, specificity 79.8%). Conclusion: The nomogram model in this study had good discrimination,calibration, and clinical benefits. It might intuitively and individually predict the risk of poor prognosis in 3 months of acute ischemic stroke, and provide a reference basis for screening the treatment plan of patients.